M.C. Higgins, the Great - Hamilton, Virginia (Hamish Hamilton Children's Books Ltd, 1974)
As a slag heap, the result of strip mining, creeps closer to his house in the Ohio hills, fifteen-year-old M.C. is torn between trying to get his family away and fighting for the home they love.
Keywords: Juvenile literature-African Americans-Dogs-Family life-Brothers and sisters-Friendship-Fiction